Knife - Nesbø, Jo, 1960- (Nesbø, Jo, 1960- Harry Hole series., 2019)
Brilliant, audaciously rogue police officer, Harry Hole from The Snowman and The Thirst, is back and in the throes of a new, unanticipated rage -- once again hunting the murderer who has haunted his entire career. Harry Hole is not in a good place. Rakel -- the only woman he's ever loved -- has ended it with him, permanently. He's been given a chance for a new start with the Oslo Police but it's in the cold case office, when what he really wants is to be investigating cases he suspects have ties to Svein Finne, the serial rapist and murderer who Harry helped put behind bars. And now, Finne is free after a decade-plus in prison -- free, and Harry is certain, unreformed and ready to take up where he left off. But things will get worse. When Harry wakes up the morning after a blackout, drunken night with blood that's clearly not his own on his hands, it's only the very beginning of what will be a waking nightmare the likes of which even he could never have imagined.